Las competencias argumentativas en la formación universitaria - Torres Ruíz, Raisa Araminta (2018)
The subject of competency-based training in higher education in Ecuador has been taking on more and more relevance in the classroom. However, the work of the argumentative powers is still relegated. This research was conducted with the objective of analyzing the different edges of the concept and demonstrate that argumentative competition, seen as a social skill is of great importance in the work, social and personal performance and as a fundamental element in the conceptual thinking of our university students and future professionals.To achieve a holistic view of this concept, the weaknesses in its attainment are decanted in the current university education, taking up the first studies in this respect and recognizing the first investigations, postulates and precursors.The research also includes a review of the research and practical definitions that are currently handled on the subject.